PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING (GBL) TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS KELAS V DI UPT SD NEGERI 5 SITIUNG: berpikir kritis - Antik Estika Hader; Raimon Efendi; Sindy Alhayyu Suci (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The problem of this study is that students have not been trained to think at a high level, this is evident based on the results of daily questions. The purpose of this study was that there were differences after the GBL model treatment was applied to students' critical thinking skills in IPAS learning in class V UPT SD Negeri 5 Sitiung. The model used is Quasi Experimental Design. That is, research that has a control group, but cannot function fully to control external variables that affect the implementation of the experiment. This research was conducted at UPT SD Negeri 5 Sitiung. The results of this study indicate that the critical thinking skills of experimental class students who use the GBL learning model. Learning is done with the Independent samples Test in hypothesis testing, showing that sig (2-tailed) is smaller than 0.003 or <0.05 so that there is a significant influence between the Game Based Learning learning model on critical thinking of IPAS learning class V UPT SD Negeri 5 Sitiung.